Humans as blood-feeding sources in sylvatic triatomines of Chile unveiled by next-generation sequencing - Esteban San Juan; Raúl Araya-Donoso; Catalina Sierra-Rosales; Juana P. Correa; Nicol Quiroga; Ricardo Campos-Soto; Aldo Solari; Martin Llewellyn; Antonella Bacigalupo; Carezza Botto-Mahan (Parasites & Vectors, 2023)
Abstract Background Triatomines are blood-sucking insects capable of transmitting Trypanosoma cruzi, the parasite that causes Chagas disease in humans. Vectorial transmission entails an infected triatomine feeding on a vertebrate host, release of triatomine infective dejections, and host infection by the entry of parasites through mucous membranes, skin abrasions, or the biting site; therefore, transmission to humans is related to the triatomine–human contact. In this cross-sectional study, we evaluated whether humans were detected in the diet of three sylvatic triatomine species (Mepraia parapatrica, Mepraia spinolai, and Triatoma infestans) present in the semiarid–Mediterranean ecosystem of Chile. Methods We used triatomines collected from 32 sites across 1100 km, with an overall T. cruzi infection frequency of 47.1% (N = 4287 total specimens) by conventional PCR or qPCR. First, we amplified the vertebrate cytochrome b gene (cytb) from all DNA samples obtained from triatomine intestinal contents. Then, we sequenced cytb-positive PCR products in pools of 10–20 triatomines each, grouped by site. The filtered sequences were grouped into amplicon sequence variants (ASVs) with a minimum abundance of 100 reads. ASVs were identified by selecting the best BLASTn match against the NCBI nucleotide database. Results Overall, 16 mammal (including human), 14 bird, and seven reptile species were identified in the diet of sylvatic triatomines. Humans were part of the diet of all analyzed triatomine species, and it was detected in 19 sites representing 12.19% of the sequences. Conclusions Sylvatic triatomine species from Chile feed on a variety of vertebrate species; many of them are detected here for the first time in their diet. Our results highlight that the sylvatic triatomine–human contact is noteworthy. Education must be enforced for local inhabitants, workers, and tourists arriving in endemic areas to avoid or minimize the risk of exposure to Chagas disease vectors. Graphical Abstract